Thrombosis risk factors in PIK3CA‐related overgrowth spectrum and Proteus syndrome. Issue 4 (6th September 2019) - Keppler‐Noreuil, Kim M.; Lozier, Jay; Oden, Neal; Taneja, Anjali; Burton‐Akright, Jasmine; Sapp, Julie C.; Biesecker, Leslie G.
Abstract: Increased risk of thromboembolism has been recognized in individuals with mosaic overgrowth disorders, Proteus syndrome (PS) and PIK3CA ‐related overgrowth spectrum (PROS), including Klippel–Trenaunay syndrome and CLOVES syndrome. PS and PROS have distinct, yet overlapping clinical findings and are caused by somatic pathogenic variants in the PI3K/AKT gene signaling pathway. PS is caused by a single somatic activating AKT1 c.49G > A p.E17K variant while PROS can be caused one of multiple variants in PIK3CA . The role of prothrombotic factors, endothelial cell adhesion molecules, and vascular malformations in both PS and PROS have not been previously investigated. A pilot study of prospective clinical and laboratory evaluations with the purposes of identifying potential risk factors for thrombosis was conducted. Doppler ultrasounds and magnetic resonance angiogram/ venography (MRA/MRV) scans identified vascular malformations in PS and PROS that were not appreciated on physical examination. Abnormal D‐dimers (0.60–2.0 mcg/ml) occurred in half of individuals, many having vascular malformations, but no thromboses. Soluble vascular endothelial markers, including thrombomodulin, soluble vascular adhesion molecule (sVCAM), soluble intercellular adhesion molecule (sICAM), E‐selectin, and P‐selectin were significantly higher in PS and PROS compared to controls. However, no single attribute was identified that explained the risk of thrombosis. Predisposition to thrombosis is likely multifactorial with risk factors including chronic stasis within vascular malformations, stasis from impaired mobility (e.g., following surgery), decreased anticoagulant proteins, and effects of AKT1 and PIK3CA variants on vascular endothelium. Based on our findings, we propose clinical recommendations for surveillance of thrombosis in PS and PROS.